Economic Growth and the Role of Taxation-Theory - Myles, Gareth D.. (OECD Economics Department Working Papers, 2009)
Economic growth is the basis of increased prosperity. This makes the attainment of growth a key objective for governments across the world. The rate of growth can be affected by policy choices through the effect that taxation has upon economic decisions and through productive public expenditures. This paper provides a self-contained introduction to the economic modelling of growth and reviews the theoretical evidence on the extent of the link between taxation and growth